2021
DOI: 10.3389/fmicb.2021.569791
|View full text |Cite
|
Sign up to set email alerts
|

Biological Soil Crust Bacterial Communities Vary Along Climatic and Shrub Cover Gradients Within a Sagebrush Steppe Ecosystem

Abstract: Numerous studies have examined bacterial communities in biological soil crusts (BSCs) associated with warm arid to semiarid ecosystems. Few, however, have examined bacterial communities in BSCs associated with cold steppe ecosystems, which often span a wide range of climate conditions and are sensitive to trends predicted by relevant climate models. Here, we utilized Illumina sequencing to examine BSC bacterial communities with respect to climatic gradients (elevation), land management practices (grazing vs. n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 87 publications
2
16
0
Order By: Relevance
“…These genera occupied more than 29 and 50% in the coremia and sclerotia, respectively, and less than 1% in soil. Allorhizobium–Neorhizobium–Pararhizobium–Rhizobium , belonging to non-cyanobacteria diazotrophic genera that are known to be associated with plant roots ( You et al, 2021 ), was the dominant genus in the sclerotia and coremia, which might support the previous speculation that cicada flower may exchange carbon and nitrogen elements in soil via endophytic bacteria to affect the content of carbon and nitrogen compounds in cicada flower ( Zeng et al, 2021 ). A previous study found that four strains of Enterobacteriaceae isolated from wild cicada flower can inhibit C. cicadae on PDA medium and increase the yield of fungal metabolites of C. cicadae ( Qu et al, 2019 ), and Enterobacteriaceae may play an important role in host fitness by resisting pathogenic microbes ( Hu et al, 2020 ), so we speculated that Enterobacteriaceae might have an inhibitory effect on C. cicadae and may help C. cicadae to resist other pathogens.…”
Section: Discussionsupporting
confidence: 71%
“…These genera occupied more than 29 and 50% in the coremia and sclerotia, respectively, and less than 1% in soil. Allorhizobium–Neorhizobium–Pararhizobium–Rhizobium , belonging to non-cyanobacteria diazotrophic genera that are known to be associated with plant roots ( You et al, 2021 ), was the dominant genus in the sclerotia and coremia, which might support the previous speculation that cicada flower may exchange carbon and nitrogen elements in soil via endophytic bacteria to affect the content of carbon and nitrogen compounds in cicada flower ( Zeng et al, 2021 ). A previous study found that four strains of Enterobacteriaceae isolated from wild cicada flower can inhibit C. cicadae on PDA medium and increase the yield of fungal metabolites of C. cicadae ( Qu et al, 2019 ), and Enterobacteriaceae may play an important role in host fitness by resisting pathogenic microbes ( Hu et al, 2020 ), so we speculated that Enterobacteriaceae might have an inhibitory effect on C. cicadae and may help C. cicadae to resist other pathogens.…”
Section: Discussionsupporting
confidence: 71%
“…Contrary to our finding, Dang et al (2020) reported that Myxococcales diminished significantly under proso millet and mung bean intercropping systems. It has been reported that Allorhizobium-Neorhizobium-Pararhizobium-Rhizobium is a rhizobia N-fixer ( You et al, 2021 ), and Bradyrhizobium is one of the genera of N-fixing bacteria in leguminous crops capable of forming symbiotic nodules, whereas Sphingomonas is widely regarded as the best environmentally friendly approach for phosphorus nutrition mobilization for plants ( Zhang et al, 2018 ). Consistently, Lindström and Mousavi (2019) identified and described these bacteria as nitrogen-fixing bacteria of legumes.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these bacterial genera have been described as essential parts of the rhizosphere microbiome in woody plants and grasses in other environments globally. For example, the genera Dyadobacter (diazotrophic bacteria), Mucilaginibacter, Asticcacaulis , and Neorhizobium (diazotrophic bacteria) are considered plant growth-promoting bacteria (PGPB) and are part of the core microbiome of diverse plants and cultivars across the globe ( Costa et al, 2006 ; Madhaiyan et al, 2010 ; Wei et al, 2017 ; Yeoh et al, 2017 ; Ishizawa et al, 2018 ; Xu et al, 2018 ; Liu et al, 2019 ; You et al, 2021 ). Strains of Devosia have been isolated from the rhizosphere of Cq and display a high tolerance to salt, where in vitro experiments have demonstrated that this bacteria can improve the osmotic and physiological performance of the Antarctic vascular plants ( Gallardo-Cerda et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%